2002
DOI: 10.1074/jbc.m109532200
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of BRG-1 Function by Brm

Abstract: The BRG-1 subunit of the SWI⅐SNF complex is involved in chromatin remodeling and has been implicated in the action of the retinoblastoma tumor suppressor (RB). Given the importance of BRG-1 in RB function, germ line BRG-1 mutations in tumorigenesis may be tantamount to RB inactivation. Therefore, in this study we assessed the behavior of cells harboring discrete BRG-1 alleles for the RB-signaling pathway. Using p16ink4a, an upstream activator of endogenous RB, or a constitutively active RB construct (PSM-RB), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
63
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 57 publications
6
63
0
Order By: Relevance
“…In a subset of mammalian SWI/SNF complexes, Brg1 is the ATPase subunit instead of Brm (49, 54 highly homologous proteins and were found to be at least partially redundant in the regulation of the cell cycle in several studies in cell culture (32,35,36,(55)(56)(57). However, the knockout of Brg1 or Brm in mice produce different phenotypes that indicate differences in their function (33,38).…”
Section: Discussionmentioning
confidence: 99%
“…In a subset of mammalian SWI/SNF complexes, Brg1 is the ATPase subunit instead of Brm (49, 54 highly homologous proteins and were found to be at least partially redundant in the regulation of the cell cycle in several studies in cell culture (32,35,36,(55)(56)(57). However, the knockout of Brg1 or Brm in mice produce different phenotypes that indicate differences in their function (33,38).…”
Section: Discussionmentioning
confidence: 99%
“…cyclin A) (31,34), the action of SWI/SNF in Plk1 regulation was investigated. The SW13 cell line does not express the BRG1 and BRM ATPases requisite for SWI/SNF activity, whereas TSUPr-1 cells express BRM and are sensitive to RB-mediated signaling (32). To activate the endogenous RB pathway, adenoviral transduction of p16ink4a that maintains RB in its hypophosphorylated/active state was utilized.…”
Section: Rb-mediated Repression Of Plk1 Is Compromised In Swi/mentioning
confidence: 99%
“…The activity of the core ATPase subunit is required by the SWI/SNF complex to regulate gene transcription (35,37,38). Prior studies have demonstrated that the combined losses of BRG1 and BRM result in resistance to the activation of the RB pathway and aberrant cell cycle progression (32,33). Additionally, the loss of SWI/SNF activity is associated with a failure of RB to elicit transcriptional repression of specific targets (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, both Brm and Brg1 are required for activation of genes such as CD44 (10) and EPO (11) and interact with prohibitin (12) and TopBP (13) for transcriptional repression. Moreover, Brg1 can functionally replace Brm and vice versa (14). Nevertheless, the presence of Brm and Brg1 in an SWI/SNF chromatin remodeling complex is mutually exclusive, and functional differences between Brm and Brg1 have been implicated from in vitro and in vivo studies.…”
mentioning
confidence: 99%